Application of knowledge management to improve organizational performance - Paroli Paroli (INFOKUM, 2024)
Knowledge management has become a critical aspect in today's information era, where organizations need to effectively manage, store, and utilize internal knowledge to achieve their business goals. This research aims to investigate the impact of implementing knowledge management on improving organizational performance. This research uses a qualitative approach with descriptive methods. The research results show that effective implementation of knowledge management in an organization can improve its performance and competitiveness. By encouraging a culture of learning, team collaboration, and knowledge sharing, and leveraging advanced knowledge management systems, organizations can be more responsive to market changes. Rewards and recognition for contributions in sharing knowledge are important factors in motivating employees. The results also show that focusing on innovation and product development by leveraging knowledge about customer needs can provide a competitive advantage. Regular knowledge audits are an important tool in evaluating implementation effectiveness, highlighting areas that require improvement to ensure the sustainability and relevance of knowledge management in supporting organizational growth.